Quantification of the effects of operative management for idiopathic scoliosis: implications for pathogenesis, pathomechanisms and future management - Pratt, Roland K. (2002)
Idiopathic scoliosis (lS) is a structural lateral curvature of the spine with rotation for which no cause is established. Surgical treatment for scoliosis focuses on the spine and achieves only partial correction of spine and trunk deformity. This correction deteriorates with time. Some pathomechanisms of deteriorating body shape are suggested from sequential anthropometry. The correction and prevention of future deterioration in body shape are the aims of any scoliosis treatment. Application of knowledge of pathomechanisms to treatment may improve outcome.